Impact of Na Doping on the Carrier Transport Path in Polycrystalline Flexible Cu2ZnSn(S, Se)4 Solar Cells. Issue 21 (27th September 2020) - Jeong, Woo‐Lim; Kim, Kyung‐Pil; Kim, Juran; Park, Ha Kyung; Min, Jung‐Hong; Lee, Je‐Sung; Mun, Seung‐Hyun; Kim, Sung‐Tae; Jang, Jae‐Hyung; Jo, William; Lee, Dong‐Seon
Abstract: It is well‐known that the alkali doping of polycrystalline Cu2 ZnSn(S, Se)4 (CZTSSe) and Cu(In, Ga)(Se, S)2 has a beneficial influence on the device performance and there are various hypotheses about the principles of performance improvement. This work clearly explains the effect of Na doping on the fill factor (FF) rather than on all of the solar cell parameters (open‐circuit voltage, FF, and sometimes short circuit current) for overall performance improvement. When doping is optimized, the fabricated device shows sufficient built‐in potential and selects a better carrier transport path by the high potential difference between the intragrains and the grain boundaries. On the other hand, when doping is excessive, the device shows low contact potential difference and FF and selects a worse carrier transport path even though the built‐in potential becomes stronger. The fabricated CZTSSe solar cell on a flexible metal foil optimized with a 25 nm thick NaF doping layer achieves an FF of 62.63%, thereby clearly showing the enhancing effect of Na doping. Abstract : The effects of Na doping on polycrystalline flexible Cu2 ZnSn(S, Se)4 (CZTSSe) solar cells are analyzed. When doping is excessive, the device shows low contact potential difference and fill factor and selects a worse carrier transport path even though the built‐in potential becomes stronger. On the other hand, the optimized CZTSSe solar cell clearly shows the enhancing effect of Na doping.